ニシ エンダビーランド アムンゼン ワン シュウヘン チガク チョウサタイ ホウコク 1998-1999 (JARE-40) - 本吉, 洋一; モトヨシ, ヨウイチ; 三浦, 英樹; ミウラ, ヒデキ; 山内, 肇; ヤマウチ, ハジメ; 吉村, 康隆; ヨシムラ, ヤスタカ; 宮本, 知治; ミヤモト, トモハル; 吉永, 秀一郎; ヨシナガ, シュウイチロウ; et al. (国立極地研究所, 1999)
P(論文) 第40次南極地域観測隊(JARE-40)は, エンダビーランド, アムンゼン湾地域において1998年12月21日から99年1月23日まで34日間の調査活動を行った。これは, 東南極リソスフェアの構造と進化研究計画(SEAL計画)の一環として計画され, 小型の観測隊ヘリコプター2機が導入された。地質および地形チームは, それぞれトナー島, リーセルラルセン山にベースキャンプを設営し, 西エンダビーランドの地学調査を試みた。しかしながら, 調査期間中に予想外の強風に見舞われ, 観測隊ヘリコプター1機が損傷を受けたために, 当初の計画を遂行することはできなかった。本報告では, 設営面での計画の立案, 準備, そして結果と問題点について, その概要を報告する。 The 40th Japanese Antarctic Research Expedition (JARE-40) conducted field operations on geology and geomorphology in the Amundsen Bay region, Enderby Land, for 34 days from December 21,1998 to January 23,1999. This was a part of the 5-year SEAL (Structure and Evolution of East Antarctic Lithosphere) project, and two helicopters were installed for field support. Geological and geomorphological teams established base camps at Tonagh Island and Mt. Riiser-Larsen, respectively, and tried to conduct surveys in western Enderby Land. At the early stage of the operation, an unexpected gusty wind destroyed one of the helicopters at Tonagh Island, and planned surveys have not been completed. This report gives details of the logistics including planning, preparation and results. departmental bulletin paper